Possibilidades de contribuição do Design Estratégico para projetos de narrativas transmídia - Alves, Silvio André Lacerda (Universidade do Vale do Rio dos Sinos, 2018)
In a world characterized by convergence, great technological evolution, strong behavioral transformations, growing informational load in a network environment and with innumerable possibilities of media support, to succeed in delivering the desired message to the user and to obtain from him the necessary attention has become one complex task. Transmedia narratives have emerged as an efficient alternative to help mitigate or eliminate such obstacles and, moreover, offer a greater degree of immersion, interaction and experience of this user. He previously consumed narratives and now begins to consume transmedia narratives. This change demonstrates a process of evolution, a change of level, in terms of communication. They are like changes in the communicational territory where the user represents a migrant that goes back and forth between media and emission-reception levels. In this sense, considering the Strategic Design the approach that facilitates the dialogue between the most diverse disciplines and capacities, a propeller of creative relations between technique and art, an alternative to offer the experiential conditions so characteristic of the solutions of transmissions storytelling, the objective of this work of research is precisely through the use of the qualitative method of the exploratory case study to investigate the possibilities of the contribution of the Strategic Design in projects of transmedia narratives. As main results, it is important to highlight the design as mediator of projects for the design of transmissive strategies, as well as in identifying and solving problems during the design process. In addition to this discussion, a frame of reference is presented to serve as an element in future reflections and experiments of communication companies in conducting communication projects, especially of transmedia narratives.
Keywords: Comunicação; Design estratégico; Narrativas transmídia; Storytelling; Experiências; Communication; Strategic design; Transmedia narratives; Storytelling; Experiences; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial